(untitled) (New York, 2009)
Real-time PCR (RT-PCR) technology is highly flexible and many alternative instruments and fluorescent probe systems have been developed recently. The decreased hands-on time, increased reliability, and improved quantitative accuracy of RT-PCR methods have contributed to the adoption of RT-PCR
Keywords: Polymerase chain reaction.,Polymerase Chain Reaction,Chuỗi phản ứng; Methods